Multiple mobility edges in quasi-periodic mosaic lattices revisited: A numerical study based on time-dependent reflection - Nguyen, Phi Ba (Communications in Physics, 2024)
The dynamics of a short wave packet in one-dimensional quasi-periodic lattices with mosaic modulated on-site potentials is investigated numerically. This model is characterized by the modulation period \(κ\) and the quasi-periodic potential strength \(λ\). For parabolic wave packets with a given central energy \(E_0\), we calculate the averaged time-dependent reflectance, \(R(t) \), for various values of κ and \(λ\). From the extensive numerical calculations, we show that there exist multiple mobility edges in such a model with the number of mobility edges to be always equal to \(2(κ-1)\).